Skin autofluorescence is associated with blood glucose levels, especially in children with type 1 diabetes - Deng, Tinghan; Wu, Jingping; Cheng, Hongbin (Frontiers in Clinical Diabetes and Healthcare, 2025)
BackgroundThis study examines the correlation between skin autofluorescence (SAF) and blood glucose levels, emphasizing the accumulation of advanced glycation end-products (AGEs). We hypothesize that SAF levels are closely linked to type 1 diabetes complications in children. The aim is to evaluate SAF’s relationship with type 1 diabetes progression in children and its potential as a non-invasive tool for disease detection and monitoring complications. The research was registered with PROSPERO (CRD42021284774).MethodsWe conducted a meta-analysis by extracting studies from databases including PubMed, MEDLINE, EMBASE, Cochrane, Science Direct, Scopus, and Web of Science. A random effects model was used to assess if SAF measurement could serve as a non-invasive marker for type 1 diabetes and its complications. SAF values were compared between children with type 1 diabetes and controls, calculating the mean difference and 95% confidence intervals.ResultsThe analysis included three case-control studies and one retrospective cohort study, all using the AGE Reader® (DiagnOptics Technologies). Data analysis showed significant heterogeneity (I² = 82%, P < 0.05). The random effects model revealed a positive correlation between higher SAF levels and type 1 diabetes in children [mean difference = 0.20 (0.16, 0.25)], indicating elevated SAF in diabetic children compared to non-diabetic peers.ConclusionThis research supports SAF measurement as a non-invasive indicator for type 1 diabetes and its complications in children. However, further studies with larger samples and longer follow-up are needed for definitive conclusions and detailed insights into complications. Additionally, the skin’s multifaceted roles require further investigation.Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42021284774.